RESTORASI CITRA PEMERINTAH KOTA JAMBI PADA KASUS â€œSISWI SMP KRITIK PEMKOT JAMBIâ€ - Maharani, Nabila; Pratiwi, Miftha (Jurnal Ranah Komunikasi, 2024)
In 2023, the Jambi City Government faced public criticism after a viral video of a junior high school student criticizing the government for allegedly allowing a large-tonnage company car to damage her grandmother's house went viral on social media. This incident led to a crisis situation due to its bad reputation which requires effective crisis management from Diskominfo Kota Jambi as government public relations. The research aimed to identify crisis management carried out by Diskominfo Kota Jambi to help Jambi City Government deal with problems related to the viral student which is deepened using Situational Crisis Communication Theory (SCCT). The qualitative approach used in the study involved in-depth interviews, observation, and documentation studies. The results showed that the crisis management at pre-crisis stage focused on problem identification and preparation. The response during crisis was classified as a strategy of reducing responsibility (diminish) by providing excuses and justification that government had no intention of creating a crisis. Diskominfo Kota Jambi also provides open and transparent clarification through websites, social media and mass media. After the crisis, the focus shifted to restoring government's reputation with positive news. There are still several steps or strategies that need to be improved in their implementation.